A New Glance at the Islamic Political Thought: A Critical View on “the History of Political Thought in Islam” - Abbas Khalaji (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2018)
This study is intended to have a critical view on “the History of Political Thought in Islam”. This book is a reference for the students and researchers of history and political sciences. The writer has explained formal, theoretical, and scientific content of the book. Then, he has tried to evaluate its features to assess its specific appropriateness to be studied and taught as a textbook for Islamic political thought. The results indicated that the book contains several advantageous properties; however, there are some formal, theoretical, and scientific shortcomings, which must be covered in the next editions in order to change the book into an appropriate and adequate source for students and researchers.